Evaluating Providers' Prescription Opioid Instructions to Pediatric Patients - Denise D. Tran; Patrick C. M. Brown; Corrin Murphy; Diana Ho; Karen A. Hudson; Anna C. Wilson; Sarah W. Feldstein Ewing (MDPI AG, 2022)
Receiving an opioid prescription during childhood increases the risk of hazardous prescription opioid (PO) use during emerging adulthood. Instruction on how to safely use POs plays an essential role in pediatric patients' capacity to utilize as well as to discontinue POs appropriately. This study aimed to evaluate pediatric PO label instructions provided to a large sample of pediatric outpatients. Data were extracted from the electronic healthcare records system identifying pediatric patients who received a PO between 2016 and 2019 from pediatric outpatient medical clinics were affiliated with a northwestern United States medical center and children's hospital. Pediatric patients (n = 12,613) between 0-17 years old who received a PO during outpatient care were included. Patients with chronic health conditions (e.g., cancer) or who received their PO from an inpatient medical setting were excluded. Patient demographics, medication instructions, associated diagnoses, and other prescription information (e.g., name of medication, dose, and quantity dispensed) were examined using automated text classification. Many label instructions did not include any indication/reason for use (20.8%). Virtually none of the POs (>99%) included instructions for how to reduce/wean off POs, contact information for questions about the POs, and/or instructions around how to dispose of the POs. Efforts are needed to ensure that pediatric PO instructions contain essential elements to improve comprehension of when and how to use POs for pediatric patients.